Thymic Epithelial Tumors as a Model of Networking: Development of a Synergistic Strategy for Clinical and Translational Research Purposes - Melis, Enrico; Gallo, Enzo; di Martino, Simona; Gallina, Filippo Tommaso; Laquintana, Valentina; Casini, Beatrice; Visca, Paolo; Ganci, Federica; Alessandrini, Gabriele; Caterino, Mauro; Cecere, Fabiana Letizia; Mandoj, Chiara; et al. (Frontiers in Oncology, 2020)
The Authors of this paper constitute a multidisciplinary clinical team involved in the management of thoracic tumors and, among them, in the management of the rare Thymic Epithelial tumors (TET). Thymoma (THY) often show a malignant behavior, relapse intrathoracically, and are difficult to management. Thymic carcinoma (TC) show from the beginning an aggressive behavior and tend to extrathoracic spread. Clinical and translational research in TET are difficult to progress due to their rarity, to the complex mixture and interplay of epithelial cells and thymocytes, leading to systemic immune derangement and to their unpredictable, often malignant behaviour. In parallel with the surgical advances leading to the widespread use of the mininvasive thymectomy by Video-assisted Thoracoscopy (VATS) and by Robotic-assisted Thoracoscopy (RATS) in addition to open access procedures, tissue-based research studies were performed. Thanks to internal collaboration with the research units at our Institute as well as to national and international networking an immunohistochemical study of angiogenetic receptors by Tissue Micro Array (TMA), the genomic characterization of the EGFR microsatellite CA-SSR-1, the preliminary mapping of genomic alterations in Thymic carcinoma and an extensive MicroRNA characterization in this tumor system were performed. Functional studies by the TC cell line TC 1899 are in progress. The recent implementation of our Biobank provides a new tool to our internal and networking collaborative research activities. Our challenge is the advancement of clinical and basic science in thymic epithelial malignancies.